Childfree In Muslim Marriage: An Islamic Family Law Perspective and Its Relevance to Premarital Education - Muhammad Tsalis Ramadlani; Fahmi Faruqi; Rocky Hasan; Muhammad Fadhlan Azka Hasya (Medan Resource Center, 2026)
The childfree phenomenon has increasingly emerged in contemporary Muslim societies as part of broader social transformations related to reproductive autonomy, changing family orientations, and shifting perceptions of marriage and parenthood. Existing studies on childfree in Islam generally focus either on normative legal debates concerning lawful (ḥalāl) and unlawful (ḥarām) rulings or on socio-cultural factors influencing reproductive choices. However, limited attention has been given to integrating Islamic family law, reproductive autonomy, and premarital education within the framework of maqāṣid al-sharīʿah. This study aims to analyze the position of childfree within Islamic family law, examine the boundaries of reproductive autonomy through maqāṣid al-sharīʿah, and explore its relevance to premarital education in contemporary Muslim societies. This research employs a qualitative normative legal method using conceptual, doctrinal, and maqāṣid al-sharīʿah approaches. Data were collected through library research from classical and contemporary fiqh literature, academic journal articles, and relevant studies on childfree and reproductive autonomy. The analysis was conducted through theme identification, categorization of legal arguments, and interpretative synthesis based on the maqāṣid framework. The findings demonstrate that the legal discourse surrounding childfree in Islam cannot be reduced merely to the binary framework of ḥalāl and ḥarām, but instead reflects a negotiation between individual reproductive autonomy and collective social welfare. This study distinguishes between temporary childfree decisions, which are relatively closer to the concept of tanzīm al-nasl and may be conditionally permissible, and permanent rejection of parenthood, which raises broader ethical concerns related to ḥifẓ al-nasl. The study further argues that the concept of mubāḥ muqayyad provides a relevant uṣūl al-fiqh framework for understanding the conditional permissibility of childfree based on considerations of maṣlaḥah and mafsadah. The novelty of this study lies in its integrative framework that connects reproductive autonomy, maqāṣid al-sharīʿah, and premarital education as an ethical model for reproductive decision-making in contemporary Muslim marriages.